Change in the Spatial Clustering of Poor Neighborhoods within U.S. Counties and Its Impact on Homicide: An Analysis of Metropolitan Counties, 1980-2010. Issue 3 (3rd July 2022) - Baumer, Eric P.; Fowler, Christopher; Messner, Steven F.; Rosenfeld, Richard
ABSTRACT: Recent scholarship has examined changes in the geographic distribution of poor persons in America, but it remains unclear whether high- and low- poverty neighborhoods have become more, or less, spatially clustered over the past several decades. Additionally, while many have argued that growth in both high-poverty spatial clusters and high-low poverty spatial clusters could yield conditions that are conducive to increases in homicide, previous research has not considered that possibility. We contribute to knowledge by examining whether there have been important shifts in the spatial clustering of poverty in America between 1980 and 2010, and if so, whether those shifts were related to changes in homicide during the period. The descriptive results of our study reveal that there were notable changes in population exposure to both high- poverty and high-low poverty spatial clusters between 1980 and 2010. Fixed-effects negative binomial regression models yield limited support for the idea that changes in spatial inequality, as measured by the clustering of high- and low-poverty neighborhoods, are associated with changes in homicide rates. In contrast, the results indicate a significant positive association between changes in exposure to very high-poverty spatial clusters and homicide trends. The findings affirm the importance of considering the spatial dynamics of demographic conditions when explaining changes in violence across communities.